Automatic water tap system / Muhammad Shafiq Abd Razak and Mohammad Shafiq Mohd Rashidi - Abd Razak, Muhammad Shafiq; Mohd Rashidi, Mohammad Shafiq (2015)
Automatic Water Tap System is a system that will control the flow out of water. The problem to find a new water source, need to pay a high water bill and the difficulty that been facing by disabled people to used water tap becomes the reason why this system is built. The system can reduce the water wasting in our daily life and save water bill so it can reduce life cost. It's also can help disabled people to used water tap in easy way. This system can be used at residence, school, mall and mosque. In this system, Arduino Uno is used as microcontroller and LDR sensor also been used to detected a user. When the sensor detects the user the system will let the water flow out. The microcontroller receives the signal from sensor and will send the signal to L239B (motor driver) to control the motor rotation. It will control the motor to rotate clock wise or anti-clock wise for open and close the water tap. The LED also been used in this system. When the green led light up, it means that the system is being used and the water is flow out. When the red led light up, it means the system is not being used so the water stop from flow out from tap. The water flows out accurately because it only flows when the sensor senses the user hand and it automatically stop the water flow when there is nobody uses the water tap. If the surrounding is dark, the yellow led will light up to illuminate the water tap area.